SPORT DEVELOPMENT INDEX ANALYSIS OF SILAT HILIR SUBDISTRICT, KAPUAS HULU DISTRICT - Noviana, Noviana; Suhairi, Muhammad; Fuzita, Mira (Sport Pedagogy Journal, 2023)
The purpose of the study. To empirically describe the Analysis of the Sport Development Index in Silat Hilir Subdistrict, Kapuas Hulu Regency.Materials and methods. The method used by the researcher is a quantitative descriptive method. The research type employed is a survey. Data collection techniques utilized in this research include direct observation, interviews, and measurement techniques. The population in this study consists of the entire population in Silat Hilir Subdistrict, Kapuas Hulu Regency, including 2 villages, namely Desa Baru and Desa Perigi, with individuals aged above 7 years, totaling 3453 people in Silat Hilir Subdistrict. Data analysis employs a quantitative approach using the Sport Development Index (SDI) analysis from the dimensions of participation and physical fitness. The sample size in this research is 30 individuals, selected from Baru Village and Perigi Village, with the criteria of 10 children (5 boys and 5 girls), 10 teenagers (5 boys and 5 girls), and 10 adults (5 men and 5 women). The age categories are 7-14 years for children, 15-24 years for teenagers, and 25-50 years for adults. The sampling technique used is stratified random sampling.Results. The research results indicate that the level of community participation in sports activities in Silat Hilir Subdistrict, Kapuas Hulu District, particularly in Perigi Village and Baru Village, as assessed by the Sport Development Index, is 0.0512188, categorizing it as "Moderate." The level of physical fitness of the community in Perigi Village and Baru Village, Silat Hilir Subdistrict, Kapuas Hulu District, as evaluated by the Sports Development Index, is 0.907, falling into the "High" category.Conclusions.It can be concluded that sports activities have an impact on the physica